Linear assembly of a porphyrin–C60 complex confined in vertical nanocylinders of amphiphilic block copolymer films. Issue 9 (16th December 2014) - Kamimura, Takuya; Komura, Motonori; Komiyama, Hideaki; Iyoda, Tomokazu; Tani, Fumito
Abstract : Linear assemblies of a 1 : 1 porphyrin–fullerene C60 complex were formed in vertical cylindrical polyether nanodomains of amphiphilic block copolymer films. Abstract : Linear assemblies of a 1 : 1 porphyrin–fullerene C60 complex were formed in vertical cylindrical polyether nanodomains of amphiphilic block copolymer films by a simple spin coating–annealing method. The nanocylinder structures were retained even with high contents of the complex in the polymer films.